OC-7 Cresentic glomerulonephritis (CGN) in childhood; classification of aetiology and clinicopathological importance of cd163 positive (M2) macrophages. (6th June 2017) - Kayki, Gozdem; Orhan, Diclehan; Ozaltin, Fatih; Talim, Beril; Düzova, Ali; Akcaoren, Zuhal; Toplaglu, Rezan; Gucer, Safak
Abstract : Crescentic glomerulonephritis (CGN) is a rare cause of glomerulonephritis in childhood. This study aims to evaluate the aetiology, demographic and histopathological data of 88 children with CGN and to investigate clinicopathological significance of CD163 expression. This retrospective study consisted of 88 children (40 girls and 48 boys) who were diagnosed as CGN between years of 2000–2015 in our centre. The expression of CD3, CD4, CD8, CD20, CD68, and CD163 in renal tissue samples and their clinicopathological correlations were investigated. The mean age was 11.49±3 years (ranging from 2 to 18 years) at the time of biopsy. Eight patients whose renal biopsies did not show any pathologic changes were chosen as control group. Their mean age was 12.6±3 years. The most common etiologic cause was Henoch-Schönlein purpura (HSP) nephritis with 26.1%, followed by lupus nephritis with 22.7% and idiopathic crescentic glomerulonephritis with 18.2%. Patients were classified into four groups (complete responder, partial responder, non-responder and end-stage renal disease) according to outcome and evaluated 51.4% of them as complete responder, 17.2% as partial responder, 14.2% as non-responder and 17% as end-stage kidney disease. Crescents were epithelial, fibroepithelial or fibrous in 72, 28.4% and 2.3% of cases, respectively. Patients with more than 50% crescents had 40% rate of end-stage kidney disease in contrast to patients with crescents less than 50% (p<0.05). In all cases, the number of CD163 positive cells of both glomerular and tubulointerstitial area were detected significantly higher than those of CD3, CD4, CD8, CD20 and CD68 positive cells (p<0.05). CD163+ cells were also significantly higher in tubulointerstitial area in patients with end stage renal disease (p<0.05). There was no correlation between severity of proteinuria, serum creatinine, glomerular filtration rate(GFR) and the number of CD163 positive cells in glomeruli and interstitium at the time of diagnosis. However, the number of CD163 positive cells in tubulointerstitial area was higher in cases with glomerular filtration rate less than 60 ml/min/1.73 m 2 after an average 3 years of follow-up (p<0.05). These findings support the role of CD163+ macrophages in tubulointerstitial injury and prognosis in CGN in childhood.